GRAPHOLOGICAL VARIATIONS IN ULYSSES POEM: A STYLISTICS ANALYSIS - Ade Namira; Rahmadsyah Rangkuti; Manugeren Manugeren (Universitas Negeri Medan, 2022)
Abstract This study aims to investigate the deployment of graphological variations in Tennyson’s poetry namely Ulysses. A Descriptive qualitative was used in this study. The data were graphological variations used in poetry and the data source was Tennyson’s Ulysses poetry consists of 70 lines. The data were analyzed based on graphological techniques and punctuation marks. The result revealed graphological variations are found in Ulysses’ poetry by Tennyson starting from capitalization, indentation to punctuation marks. Capitalization was used to indicate proper noun and used in every line as a rule of nineteenth century poetry. For indentation, it was found two lines with more indented line than others. Lastly, five distinct family of punctuation marks were used namely stops: period, colon, semi-colon, and comma, tonal indicators: exclamation mark, sign of omission: apostrophe, rules: hyphen and em-dash, and combinate-mark: commash. Those graphological variations closely related with the era of the poet wrote his poetry.Keywords: Analysis; Graphology; Poetry; Ulysses AbstrakPenelitian ini bertujuan untuk mengetahui penggunaan variasi grafologi dalam puisi Tennyson dengan judul Ulysses. Metode deskriptif kualitatif digunakan dalam penelitian ini. Data yang digunakan adalah variasi grafologi yang digunakan dalam puisi dan sumber datanya adalah puisi Ulysses karya Tennyson yang terdiri dari 70 baris. Data dianalisis berdasarkan teknik grafologi dan tanda baca. Hasil penelitian menunjukkan bahwa variasi grafologi ditemukan dalam puisi Ulysses karya Tennyson mulai dari penggunaan huruf kapital, indentasi hingga tanda baca. Kapitalisasi digunakan untuk menunjukkan kata benda yang tepat dan digunakan di setiap baris sebagai aturan puisi abad kesembilan belas. Pada indentasi ditemukan dua baris puisi yang lebih menjorok dari yang lain. Terakhir, lima tanda baca yang berbeda digunakan yaitu perhentian: titik, titik dua, titik koma, dan koma. Kemudian, indikator nada: tanda seru, tanda penghilangan: apostrof. Selanjutnya aturan: tanda hubung dan tanda pisah, dan tanda kombinasi: koma. Variasi grafologi tersebut erat kaitannya dengan zaman penyair menulis puisinya.Kata kunci: Analisis; Grafologi; Puisi; Ulysses